2011
DOI: 10.1007/s10266-011-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease as a risk factor for adverse pregnancy outcomes: a systematic review and meta-analysis of case–control studies

Abstract: Periodontal disease is a highly prevalent group of illnesses of microbial etiology, whose consequence is a severe breakdown of tooth-supporting structures. A link between periodontal infection and several systemic conditions, among which adverse pregnancy outcomes, has been suggested in the recent years. The aim of this review based on case-control studies was to evaluate if periodontal disease could be considered as a risk factor for preterm birth, low birth-weight and preterm low birth-weight. An electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 48 publications
1
77
0
8
Order By: Relevance
“…So, the findings of this study also suggest that pregnant women do not concern receiving information about how to take oral care. Other studies have also shown that pregnant women's awareness in the field of oral care is very partial (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…So, the findings of this study also suggest that pregnant women do not concern receiving information about how to take oral care. Other studies have also shown that pregnant women's awareness in the field of oral care is very partial (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of oral health in ensuring positive pregnancy outcomes is acknowledged (1)(2)(3)(4)(5). Nevertheless, hormonal alterations affecting oral health during pregnancy cannot be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations may impose a burden on many women, leading them to neglect their general and oral health. There is a positive association between oral health problems such as periodontitis and adverse pregnancy outcomes such as preterm birth and eclampsia, and good oral health can reduce the risk of these outcomes (1)(2)(3)(4)(5). In the same context, several factors are known to be associated with children's oral health status, including maternal oral health knowledge and status, education, occupation and age (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that intraoral infections may be associated with adverse pregnancy outcomes (1–5). However, there is no conclusive evidence on these associations (6,7). Some adverse consequences of oral diseases (eg, tooth loss, pain) can be avoided by early treatment during regular dental visits.…”
Section: Introductionmentioning
confidence: 99%